Design and Build of Posyandu Service Application at Posyandu Yanita - Ricky Irawan; Sri Poedji Lestari; Bernadus Gunawan Sudarsono (Akademi Manajemen Informatika dan Komputer Widya Loka Medan, 2023)
Posyandu Yanita is a form of Community-Based Health Efforts (UKBM) which is managed and organized, by the village, for and with the community in implementing health development, in order to empower the community and provide convenience to the community in obtaining basic health services to accelerate the reduction of maternal mortality and baby. Posyandu Yanita experienced input errors and data changes because the work was still manual so it would require a lot of paper to replace new ones, and Posyandu Yanita had difficulty finding the information needed in a short time. Based on these problems, the Android-based Yanita Posyandu information system was designed using the analysis and design method using the Unfield Modeling Language (UML). The Yanita Posyandu information system uses the Dephi and HeidiSql programming languages ??as its database. With the Yanita Posyandu information system, related processes become easier to use, accurate and integrated.